Demam Tifoid disertai Ankilostomiasis pada Anak Usia 5 Tahun: Sebuah Laporan Kasus - Muhammad Morsa Habibie; Oktadoni Saputra (CV. Jasa Sukses Abadi, 2026)
Typhoid fever remains one of the most common infectious diseases affecting children in developing countries, particularly in areas with poor sanitation and hygiene. Meanwhile, hookworm infection continues to be a significant public health problem because it may cause chronic blood loss, iron deficiency anemia, malnutrition, and impaired growth in children. The coexistence of these two infections may aggravate clinical manifestations and requires a comprehensive diagnostic and therapeutic approach. This case report aims to describe the clinical presentation, diagnostic evaluation, and management of typhoid fever accompanied by hookworm infection in a child. A 5-year-11-month-old girl was admitted to the Emergency Department of dr. H. Abdul Moeloek Regional Hospital with a two-week history of fever accompanied by abdominal pain, vomiting, and diarrhea. Physical examination revealed fever, pale conjunctiva, and abdominal distension. Laboratory investigations demonstrated microcytic hypochromic anemia, leukocytosis, thrombocytosis, and hypoalbuminemia. Serological testing for anti-Salmonella IgM (TUBEX) yielded a positive result with a score of 6, while stool examination identified Ancylostoma duodenale eggs. The patient was diagnosed with typhoid fever and hookworm infection and was treated with intravenous antibiotics, an anthelmintic agent, supportive therapy, adequate fluid and nutritional management, and education regarding personal hygiene and sanitation. During hospitalization, the patient's clinical condition gradually improved, as evidenced by the resolution of fever, abdominal pain, vomiting, and diarrhea, along with improved tolerance to oral intake, and she was discharged in good condition. This case highlights the importance of considering coinfection in children presenting with prolonged fever, anemia, and poor sanitation-related risk factors. An integrated approach involving accurate diagnosis, appropriate antimicrobial and anthelmintic therapy, nutritional support, and preventive education is essential to improve clinical outcomes and reduce the risk of complications and reinfection.